2014
DOI: 10.1098/rsfs.2013.0074
|View full text |Cite
|
Sign up to set email alerts
|

Modelling mammalian cellular quiescence

Abstract: One contribution of 10 to a Theme Issue 'Computational cell biology: from the past to the future'. Cellular quiescence is a reversible non-proliferating state. The reactivation of 'sleep-like' quiescent cells (e.g. fibroblasts, lymphocytes and stem cells) into proliferation is crucial for tissue repair and regeneration and a key to the growth, development and health of higher multicellular organisms, such as mammals. Quiescence has been a primarily phenotypic description (i.e. non-permanent cell cycle arrest) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
166
0
6

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 150 publications
(175 citation statements)
references
References 153 publications
(200 reference statements)
3
166
0
6
Order By: Relevance
“…Since quiescent cells are recently thought to be distinct from cycling cells or cell cycle arrested cells, we speculate the phenotype seen in hypoxic cell subsets is mainly quiescence showing “a state of cell cycle arrest” that enables cells to re-enter a proliferating state after transient arrest (Yao, 2014). This is supported by the studies on suppression of conversion from arrest to senescence by hypoxia (Blagosklonny, 2013; Leontieva et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since quiescent cells are recently thought to be distinct from cycling cells or cell cycle arrested cells, we speculate the phenotype seen in hypoxic cell subsets is mainly quiescence showing “a state of cell cycle arrest” that enables cells to re-enter a proliferating state after transient arrest (Yao, 2014). This is supported by the studies on suppression of conversion from arrest to senescence by hypoxia (Blagosklonny, 2013; Leontieva et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…This is supported by the studies on suppression of conversion from arrest to senescence by hypoxia (Blagosklonny, 2013; Leontieva et al, 2012). Moreover, the tendency of diverse patterns of CFSE dye profile under different oxygen tensions could also denote the heterogeneous quiescent states, leading to heterogeneous proliferation (Yao, 2014). …”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, by testing much higher hydroquinone concentrations, we observed a relatively weak cytotoxicity in lymphocytes. This was not a surprise, considering that lymphocytes are "stuck" in the G 0 phase of the cell cycle, characterized by the slowing down of many intracellular processes (49,50). The majority of dead cells we detected Jurica K et al In vitro assessment of the cytotoxic, DNA damaging, and cytogenetic effects of hydroquinone in human lymphocytes Arh Hig Rada Toksikol 2017;68:322-335 using EtBr/AO staining died via apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…We found that the cytotoxicity in quiescent fibroblasts was associated with the reduction of quiescence depth as indicated by the increased basal activity of the Rb-E2F bistable switch [2123]. Since quiescence provides a protection against cellular stress and toxicity [24, 25], the shallowing of the quiescence state led to the sensitization of cells to quiescence exit and apoptosis.…”
Section: Introductionmentioning
confidence: 99%